Dimissorial letters in the Code of Canons of the Eastern Churches - TANASIYCHUK, ANDRIY (Prawo Kanoniczne, 2017)
The present study is dedicated to the administrative act of the competent person, who has the right to release dimissorial letters by exercising the proper governance in the Church. This document is necessary for the licit administration of the sacrament of Holy Orders. The eastern legislation that regulates the life of the Eastern Catholic Churches contains a vast number of such ecclesiastical subjects that are provided by the Supreme Legislator with the right to issue such a document. In addition, the Eastern canon law in its rules concerning the sacraments also show the liturgical nature of their celebration. Therefore it can be said that there is a strong and mutual relationship between the canonical norms and the liturgical rubrics among the Eastern Churches.